IN VIVO AND IN VITRO INVESTIGATIONS OF PHARMACOLOGICAL POTENTIALS OF CASSIA OBTUSIFOLIA PLANT - SM, KEWATKAR; VV, PAITHANKAR; SS, BHUJBAL; SP, JAIN; DH, NAGORE (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objectives: Cassia obtusifolia L. belonging to the Family Caesalpiniaceae, proposed to have abundant pharmacological potential and widely consumed as laxative, diuretic, and stomachic. The aim of the present research was to study the anti-inflammatory, analgesic, antipyretic, and antioxidant potentials of C. obtusifolia plant. Methods: Various acute and chronic animal models such as Carrageenan-induced paw edema, tail immersion method, acetic acid-induced writhing, and in vitro methods were used to study the profound pharmacological and antioxidant potentials. Results: The results for pharmacological study were statistically analyzed by one-way ANOVA followed by Dunnett’s multiple comparisons using INTA software. Conclusion: The present study reveals that C. obtusifolia possesses comparable anti-inflammatory, analgesic, antipyretic, and antioxidant potential.